Selecting Materials for Environmental-Friendly Buildings: The Need for Improved Environmental Impact Data - Nachawit T. (Institute of Research and Community Outreach - Petra Christian University, 2012)
Buildings of the future need to be more environmental-friendly. Selecting environmentally-benign materials in design stage would partly help achieving such goal. Examination of existing environmental impact data of building materials reveals that the data differ greatly from one source to another. Comparisons of environmental impact values of selected materials are presented. The sources that give rise to data variation are identified and discussed. The applicability of existing data is assessed from the designers’ perspective. Limitations of current practice in data acquisition and presentation are also discussed. It is concluded that existing environmental impact data of building materials are inconsistent and perplexing to designers. An alternative approach to data acquisition and presentation is to break the life cycle of building materials into several phases and to calculate the total impact value as the sum of the impacts of all phases. This would make the determination of the full life cycle value feasible and increase external validity of research results.